Nauczyciel(-ka) akademicki(-a) w (auto)metaforze - Bochno, Ewa (Adult Education Discourses, 2020)
The Author conducts a higher education review by using metaphors obtained from young tutors regarding their professional and scientific situation. She shows the inhomogeneous and sometimes even internally contradictory character of the relations within a university as well as the relations between a university and the environment. The author reflects on the culture of higher education as well as its internal and external conditions of functioning. The Author presents the results of a small survey she collected using the snowball sampling technique. It is an analysis of written statements in which the respondents defined their professional and scientific situation with a metaphor. This is a presentation of the basic problems faced by young university employees.